Lipid Metabolism in the Development and Progression of Vascular Cognitive Impairment: A Systematic Review - Qin, Qi; Yin, Yunsi; Xing, Yi; Wang, Xuan; Wang, Yan; Wang, Fan; Tang, Yi (Frontiers in Neurology, 2021)
Background: Vascular cognitive impairment (VCI) is a major public health problem. The current diagnosis of VCI is made based on the assessment of clinical symptoms and neuropsychological measurements and supported by neuroimaging. These methods are both time-consuming and expensive, which leads to discoveries of other biomarkers for VCI. Metabolomics is an emerging and powerful tool to discover of new biomarkers of disease, which can investigate variations in different metabolic processes such as lipid. Since the brain is highly enriched in lipids and that lipid changes may readily lead to pathology in the brain. VCI is vulnerable to the disturbance of lipid metabolism. Furthermore, blood samples, which could be identified as reliable clinical biomarkers are relatively convenient to obtain and provide a non-invasive assessment approach. Therefore, our study aims to understand whether peripheral lipid biomarkers can be used as diagnostic biomarkers and monitor the progression of VCI. Method: We systematically searched the PubMed, Embase, CNKI and VIP databases to find VCI and lipid metabolism in reports from inception through February 2021. Studies meeting the following criteria were eligible: (1) original studies in humans; (2) lipid metabolites in blood; (3) reports of VCI. Result: Through our review, 9 original articles were eligible. Blood-based metabolites that might be potential biomarkers were identified. Most of them including PC, PE, Cers and ChEs were significantly lower, while elevation of FAs and DGs were associated with VCI. Most importantly, these blood-based metabolites might be proposed as potential biomarkers for VCI, which provides direction for further validation. Discussion and conclusion: To the best of our knowledge, this is the first systemic review concerning the relationship of lipid metabolism and VCI. It identifies potential biomarkers and provides insights into the disease pathobiology. However, more advanced studies and researches on a lipidomic platform must be done to understand the exact pathology behind this and identify potential lipid biomarkers, which might help achieve the ultimate goal of discovering novel therapeutics.